AN OVERLAP OF GUILLAIN-BARRÉ SYNDROME, MILLER-FISHER SYNDROME, AND BICKERSTAFF BRAINSTEM ENCEPHALITIS PRESENTING AS CLINICAL BRAIN DEATH, A CASE SERIES - AWAD, AHA; RANA, MA; MADY, AF; AHMED, M; SADIQ, HZ; DAHSHAN, A; ABUANZA, IAM (Biological and Clinical Sciences Research Journal, 2024)
Guillain-Barré Syndrome (GBS), Miller-Fisher Syndrome (MFS), and Bickerstaff Brainstem Encephalitis (BBE) are neuroinflammatory disorders that share common immunopathogenic mechanisms. Although overlapping presentations of these conditions are rare, they pose significant diagnostic challenges, especially when mimicking clinical brain death. Objective: To present a case series of three patients who demonstrated an overlap of GBS, MFS, and BBE, with all patients exhibiting profound neurological impairments, including clinical signs of brain death. Methods: A retrospective review of three cases admitted to the ICU over the last three years was conducted. Detailed clinical profiles, cerebrospinal fluid (CSF) analysis, nerve conduction studies (NCS), and electromyography (EMG) results were reviewed. All patients were treated with intravenous immunoglobulins (IVIG) and therapeutic plasma exchange (TPE). Results: All three patients had a history of preceding infections and were presented with ophthalmoplegia, ataxia, and altered levels of consciousness, progressing to coma. CSF analysis revealed albuminocytological dissociation, and NCS/EMG indicated severe polyneuropathy. Two patients responded positively to IVIG and plasmapheresis, showing significant neurological recovery, while the third patient demonstrated a delayed but spontaneous recovery. All patients eventually achieved full or near-full neurological recovery. Conclusions: This case series highlights the clinical continuum and diagnostic complexity of overlapping GBS, MFS, and BBE, particularly in presentations mimicking brain death. Early recognition and prompt immunomodulatory therapy are crucial in improving patient outcomes, even in cases with severe neurological deficits. Further research is warranted to elucidate pathophysiology and optimize treatment strategies for overlapping neuroinflammatory syndromes.